Microstructural properties and surface roughness of 3D printed open cell-foam - Shikh Anuar, Fadhilah; Mustapha, Khairul Azhar; Mohd Sa'at, Fatimah Al Zahrah; Mohd Zini, Nurul Hilwa; Mat Tokit, Ernie; Narasimmanaidu, Satishwara Rao; Hooman, Kamel (Malaysian Tribology Society, 2023)
In this study, the microstructure of open-cell metal foam was generated and reconstructed, to produce a new generation of open-cell foam, which is called 3D printed open-cell foam. At the current stage of research, nylon powder and plastic acid are utilized as the materials for two different 3D printing technologies: Selective Laser Sintering (SLS) and Fused Deposition Modelling (FDM), respectively. The microstructural properties and surface roughness of the 3D printed open-cell foam are investigated using CAD files and microscope images. The surface smoothness and structure strength are found to be dependent on the printing technologies, material employed, and foam size. However, the SLS technology produced smoother ligament surfaces with fewer residues than using the FDM. The ligaments of the small-size 3D printed open-cell foam at the exact size of the metallic foam, on the other hand, are weak and easily shattered. This study also found that the trends of pressure drop from additive manufacturing methods agreed to the original metallic open-cell foam, which are decreasing with the increase of pore sizes.